The Effect of Profitability (ROE), Capital Structure (DER) and Firm Size on Firm Value (PBV) (Case Study on Primary Consumer Goods Manufacturing Companies Listed on the Indonesia Stock Exchange 2016-2018 Period) - Jajang Romansyah; Mochamad Zakaria; Maria Lusiana Yulianti (Journal of Accounting and Finance Management, 2021)
The purpose of this study is to find out an overview of profitability (ROE), capital structure (DER), firm size and firm value (PBV) in Primary Consumer Goods sector companies listed on the Indonesia Stock Exchange for the 2016-2018 period. And to find out an overview of the effect of profitability (ROE), capital structure (DER) and firm size on firm value (PBV) in Primary Consumer Goods sector companies listed on the Indonesia Stock Exchange partially and simultaneously for the 2016-2018 period. The research method used in this study is a quantitative method. The population in this study are Primary Consumer Goods sector companies listed on the Indonesia Stock Exchange during the 2016-2018 period with a total of 60 companies, and the research sample is 41 companies with the criteria or considerations used in research such as companies that have positive net income for the period 2016-2018. The result of this research is that profitability (ROE) tends to decrease, the capital structure (DER) fluctuates, the size of the company shows an increase, while the company value (PBV) fluctuates every year. Profitability (ROE) has an effect on firm value (PBV), capital structure (DER) has an effect on firm value (PBV) and firm size has an effect on firm value (PBV) in Primary Consumer Goods sector companies listed on the Indonesia Stock Exchange for the period 2016-2018. Profitability (ROE), capital structure (DER) and company size simultaneously have an effect on firm value (PBV) in Primary Consumer Goods sector companies listed on the Indonesia Stock Exchange for the 2016-2018 period.